2020
DOI: 10.1155/2020/2976535
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors Measure Ankle Joint Changes of Patients with Parkinson’s Disease before and after Acute Levodopa Challenge

Abstract: Background. Previous studies found levodopa could improve the activity of the ankle joints of patients with Parkinson’s disease (PD). But ankle joint movement is composed of four motion ranges. The specific changes of four motion ranges in PD remain unknown. Objective. The purpose of this study was to decompose the complex ankle joint movement, measure ankle joint changes before and after the acute levodopa challenge test (ALCT), and investigate the effects of these parameters on gait performance. Methods. 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…The PIGD group exhibited smaller TO angle and ROM-AJ than the TD group. These results are in line with recent works that the AJ movement is decreased in PD, 3 and patients with PIGD have severely impaired distal movements. 21 The decreased TO and HS angles indicate a reduced foot clearance and may result in tripping.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The PIGD group exhibited smaller TO angle and ROM-AJ than the TD group. These results are in line with recent works that the AJ movement is decreased in PD, 3 and patients with PIGD have severely impaired distal movements. 21 The decreased TO and HS angles indicate a reduced foot clearance and may result in tripping.…”
Section: Discussionsupporting
confidence: 93%
“…31 HS angle is decreased whereas TO is not reduced in patients with PD. 3,12,32 However, in our study, the HS of both PD subtypes showed no difference. TO was remarkably decreased in the PIGD group.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…According to this observation, the index resulted able to represent the articular mobility of lower limbs, in which a lower TDI is related to higher mobility and vice versa. Studies generally agree about the fact that the joint ROMs are larger in the healthy population than in PD patients 40,41 .…”
Section: Tdi and Kinematic Parametersmentioning
confidence: 89%